PENGARUH STORY TELLING TERHADAP TINGKAT KECEMASAN ANAK PRASEKOLAH YANG MENJALANI HOSPITALISASI DI RSUP DR.M.DJAMIL PADANG TAHUN 2017 - Amelia Susanti; hendika safitri (STIKes ALIFAH PADANG, 2017)
Storry telling is a non-pharmacological therapy that aims to make children happy so as to reduce anxiety levels in children. This study aims to determine whether there is influence story telling on the anxiety level of preschool children who underwent hospitalization in Dr.M.DJAMIL Padang Hospital Year 2017.Type of this research is Quasi experiment with approaches One group pretest and posttest. The research was conducted in 16 until 30 august 2017. The population in this study is infinite, the number of samples in this study were 10 Preschool children who underwent hospitalization at Dr.M.DJAMIL Padang Hospital with various disease. the sampling technique used insidental sampling. Instrument the research using observation sheet (The results of anxiety level measurement).Before Storry Telling therapy was found as many as 4 people (40%) children experience high levels of anxiety and as many as 6 people (60.0%) of children experience moderate anxiety level. After Storry Telling therapy was found as many as 2 people (20.0%) children experience moderate anxiety level and as many as 8 people (80.0%) of children experience low anxiety levels. There is influence story telling to the level of anxiety of preschool children who undergo hospitalization in Dr.M.DJAMIL Padang Hospital in 2017 (p = 0,007).Can be concluded that the level of anxiety in children can be reduced by doing storry telling therapy. It is recommended that health care workers take care of children to implement story telling therapy in children so as to reduce anxiety levels in children.Penelitian ini bertujuan untuk mengetahui apakah ada pengaruh story telling terhadap tingkat kecemasan anak prasekolah yang menjalani hospitalisasi di RSUP Dr.M.DJAMIL Padang Tahun 2017.Jenis penelitian ini menggunakan pra-eksperiment dengan pendekatan one group pretest-posttest Design. Penelitian telah dilakukan pada tanggal 16 – 30 Agustus 2017. Populasi dalam penelitian ini bersifat infinit, jumlah sampel adalah 10 orang anak usia prasekolah yang menjalani hospitalisasi di ruang akut dan kronik di RSUP Dr.M.DJAMIL Padang. 40% anak mengalami tingkat kecemasan tinggi, 60.0% anak mengalami tingkat kecemasan sedang. Sesudah terapi Storry Telling ditemukan 20.0% anak mengalami tingkat kecemasan sedang dan 80.0% anak mengalami tingkat kecemasan rendah. Ada pengaruh story telling terhadap tingkat kecemasan anak prasekolah yang menjalani hospitalisasi di RSUP Dr.M.DJAMIL Padang Tahun 2017 (p = 0,007). Dapat disimpulkan bahwa tingkat kecemasan pada anak dapat dikurangi dengan melakukan terapi storry telling . Disarankan kepada petugas kesehatan yang merawat anak untuk menerapkan terapi story telling pada anak sehingga dapat menurunkan tingkat kecemasan pada anak.